Inutero bisphenol A concentration, metabolism, and global DNA methylation across matched placenta, kidney, and liver in the human fetus. (April 2015) - Nahar, Muna S.; Liao, Chunyang; Kannan, Kurunthachalam; Harris, Craig; Dolinoy, Dana C.
Highlights: BPA is found in matched human fetal liver, kidney and placenta. BPA-specific metabolic profiles are similar across tissue. BPA-associated alterations to global methylation occur in placenta. Abstract: While urine has been an easily accessible and feasible matrix for human biomonitoring, analytical measurements in internal tissues and organs can provide more accurate exposure assessments to understand disease etiology. This is especially important for the endocrine active compound, bisphenol A (BPA), where studies investigating internal doses at sensitive periods of human development are currently lacking. Herein, BPA concentrations, BPA-specific metabolizing enzyme gene expression, and global DNA methylation were characterized across three matched tissues from elective pregnancy terminations of 2nd trimester human fetuses: the placenta, liver, and kidney ( N = 12 each; N = 36 total). Compared to liver (free: 0.54–50.5 ng g −1 ), BPA concentrations were lower in matched placenta (<0.05–25.4 ng g −1 ) and kidney (0.08–11.1 ng g −1 ) specimens. BPA-specific metabolism gene expression of GUSB, UGT2B15, STS, and SULT1A1 differed across each tissue type; however, conjugation and deconjugation expression patterns were similar across the fetus. Average LINE1 and CCGG global methylation were 58.3% and 59.2% in placenta, 79.5% and 66.4% in fetal liver, and 77.9% and 77.0% in fetal kidney, with significant tissue-specific DNA methylation differences in both LINE1 ( p -value <0.001) and CCGG content ( p -value <0.001). Total BPA concentrations were positively associated with global methylation for the placenta only using the LINE1 assay ( p -value: 0.002), suggesting organ-specific biological effects after fetal exposure. Utilizing sensitive human clinical specimens, results are informative for BPA toxicokinetics and toxicodynamics assessment in the developing human fetus.